KEKUATAN PEMBUKTIAN AKTA DIBAWAH TANGAN YANG DILEGALISASI OLEH NOTARIS DALAM SENGKETA PERDATA - , Bahruddin Tampubolon; , Sigit Riyanto, SH.,M.Si., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The goal of this research is to determine the Notary responsibility about the truth of deed under the hand legalized, and the verification power of deed under the hand legalized by notaries as evidence in court. This research is a normative juridical research, namely the law research done by researching the references or secondary data. Normative law research is a law research conducted by examining the principles of law, law systematic, and law synchronization by analyzing it. All data is then analyzed by qualitative descriptive method. The results of this research are: (1) a letter under the hand though it has got legalization from notaries, it is still a letter that is created under the hand. Legalization is an endorsement letter made under the hand. About legalization Section 1874 KUHPerdata (Civil Code) states